Lenovo Acquired Motorola Mobility in a Bipolar World of Mobile phone makers - Singh, Netra Pal (Industrija, 2017)
This paper presents an analysis of key points of Lenovo and Motorola deal such as approval of the deal by regulatory bodies in the United States and China, pricing and payment terms of the deals, positive and negative side of the deal for Google and Lenovo in the present context and in future, impact on the smartphone markets in China and world, possibilities of Lenovo making it a repeat of acquiring ThinkPad business of IBM during 2004 or will get rid of Motorola like Google. The analysis is based on qualitative and time series quantitative data compiled from different sources. The quantitative data are mainly consists of changes in different parameters of mobile phone business before and after the acquisition of Motorola Mobility by Lenovo. The quantitative data are analyzed with respect to different growth parameters of mobile phone business of major manufacturers. Research paper also attempts to find answers to few specific research questions with respect to impact on eco-systems of Google and Lenovo technologies. Based on analysis, it is inferred that becoming a successful organization in device manufacturing in an industry which is highly competitive, work with low margins, and maturing is becoming difficult with passing time.